Penerapan Model Contextual Teaching and Learning pada Pembelajaran IPS Kelas - Ratina, Ratina; Valen, Andri; Krisnawati, Yuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the completeness of student learning outcomes after applying the contextual teaching and learning model in social studies learning for grade V of SD Negeri 85 Lubuklinggau. This type of research is quantitative with the experimental method used being the pre-experimental design method. The experimental design used is in the form of pre-test post-test and group design. The data collection technique in this study uses a test. The test is in the form of 13 multiple-choice questions. Data analysis techniques with steps: average score and standard deviation, normality test, and z-test. The average pre-test score is 56.60 and the average post-test score is 79.92 with a percentage of students who complete it of 79%. Based on the z-test analysis, the Zcount value (3.74) and Ztable (1.64) are obtained if compared, then Zcount> Ztable. For the final test at a significant level of α = 0.05, it can be concluded that the learning outcomes of social studies of grade V students of SD Negeri 85 Lubuklinggau after implementing the Contextual Teaching and Learning learning model were significantly complete. Keywords: Contextual Teaching and Learning, Learning Outcomes, Social Studies, Implementation